Evaluation of Topical Anti-Inflammatory Effects of a Gel Formulation with Plantago Lanceolata, Achillea Millefolium, Aesculus Hippocastanum and Taxodium Distichum - Anca Zanfirescu; Georgiana Nitulescu; Gheorghe Stancov; Denise Radulescu; Cosmin Trif; George Mihai Nitulescu; Simona Negres; Octavian Tudorel Olaru (MDPI AG, 2020)
Medicinal plants hold a significant place as alternative treatments available for inflammatory diseases, with many phytoconstituents being frequently tested in vitro for their biological activities. In the current study, we investigated the in vivo anti-inflammatory properties of a novel active gel formulation, combining Achillea millefolium and Taxodium distichum essential oils with extracts of Aesculus hippocastanum seeds and Plantago lanceolata leaves. The toxicity of the obtained extracts and volatile oils was determined using the invertebrate model based on Daphnia magna. Anti-inflammatory potential was evaluated by the plethysmometric method on Wistar rats, expressed as the inhibition of the inflammatory oedema (%IIO), while the antinociceptive response was determined on NMRI mice, according to the tail-flick latency method. The tested gel's efficacy was similar to the 5% diclofenac standard (maximal %IIO of 42.01% vs. 48.70%, respectively), with the anti-inflammatory effect being observed sooner than for diclofenac. Our active gel also produced a significant prolongation of tail-flick latencies at both 60 and 120 min, comparable to diclofenac. Consequently, we can imply that the active constituents present in vivo anti-inflammatory properties, and the prepared gel may be suited for use as an alternative treatment of topical inflammatory conditions.